Soluble Triggering Receptor Expressed on Myeloid Cells 1 Is Released in Patients with Stable Chronic Obstructive Pulmonary Disease - Markus P. Radsak; Christian Taube; Philipp Haselmayer; Stefan Tenzer; Helmut R. Salih; Rainer Wiewrodt; Roland Buhl; Hansjörg Schild (Clinical and Developmental Immunology)
Chronic obstructive pulmonary disease (COPD) is increasingly recognized as a systemic disease that is associated with increased serum levels of markers of systemic inflammation. The triggering receptor expressed on myeloid cells 1 (TREM-1) is a recently identified activating receptor on neutrophils, monocytes, and macrophage subsets. TREM-1 expression is upregulated by microbial products such as the toll-like receptor ligand lipoteichoic acid of Gram-positive or lipopolysaccharides of Gram-negative bacteria. In the present study, sera from 12 COPD patients (GOLD stages I–IV, FEV1 51 ± 6%) and 10 healthy individuals were retrospectively analyzed for soluble TREM-1 (sTREM-1) using a newly developed ELISA. In healthy subjects, sTREM-1 levels were low (median 0.25 ng/mL, range 0–5.9 ng/mL). In contrast, levels of sTREM-1 in sera of COPD patients were significantly increased (median 11.68 ng/mL, range 6.2–41.9 ng/mL, P<.05). Furthermore, serum levels of sTREM-1 showed a significant negative correlation with lung function impairment. In summary, serum concentrations of sTREM-1 are increased in patients with COPD. Prospective studies are warranted to evaluate the relevance of sTREM-1 as a potential marker of the disease in patients with COPD.